A interiorização das instituições de ensino superior: uma análise dos custos da graduação no campus IV da UFPB. - Falcão, Cibele Maria Botto (2017)
Cost-per-student information provides educational institutions with an important tool for budgeting and for the population to assess the efficiency of public spending. Higher quality education plays a strategic role for the country's economic and social development and contributes to the reduction of social and regional inequalities. Therefore, in 2003, the Federal Government began to expand federal higher education institutions in compliance with the National Education Plan (PNE). In order to evaluate the costs of this internalization policy for the state of Paraíba, a cost survey was carried out per student attending undergraduate courses at Campus IV of the Federal University of Paraíba (UFPB) in the period from 2009 to 2015. The base of the data used was the budget executed (current and capital expenses) of the institution, with resources from the Treasury and own resources. The treatment of costs occurred through the system that absorbs the fixed and variable costs, whether direct or indirect (cost by absorption) of the Costs Centers and the regime of competence. It was observed that most of the costs are with technical and teaching staff, and in 2009 they accounted for 57.34% of the direct expenses incurred on campus IV, and in the year 2015 they represented almost all of these costs expenditure, about 94.52%. In this context, the Department of Social Sciences (Anthropology and Indigenous Cultures) stood out as the one with the highest cost per student inside the campus IV, accounting for the importance of R $ 31,204.64, as an annual expense per student enrolled in the course. It was also verified that the Department of Applied Social Sciences (Accounting Sciences and Executive Bilingual Secretariat) presented the lowest annual cost per student of campus IV in 2015, in the amount of R $ 11,102.14. In addition, it should be noted that the high dropout rates present in the courses greatly increase the annual cost per graduate student (in the case of Anthropology an increase of R $ 190,685.62). The annual cost per diploma in the Department of Applied Social Sciences reaches R $ 25,818.94 (Accounting Sciences) and R $ 33,642.86 for the Bilingual Executive Secretariat course; As for the Department of Social Sciences, the annual cost per graduated student reaches R $ 222,890.26 (Anthropology and Indigenous Cultures).